Figurative Language in Love and Deepspace Instagram Advertisements - Mathilda Regina Tjahjahadi Taslim (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study analyzes the use of figurative language in Instagram advertisement posts by the official Love and Deepspace account. The aim of this study is to identify the types of figurative language based on Harris’ (2018) figurative language theory and explore their meanings within the context of each Instagram post. A qualitative method was applied to analyze 40 Instagram posts. Data collection involved selecting relevant posts, taking screenshots, and collecting sentences containing figurative language. These were categorized according to Harris’ (2018) theory, while Jackson’s (2013) theory of denotation and connotation was used to interpret meaning. Each sentence was also examined alongside visual content to understand how language and imagery work together to convey meaning. The results show that the advertisements used simile, metaphor, metonymy, personification, allusion, and transferred epithet. The figurative language in these advertisements helps build emotional connections, enhance storytelling, create memorable experiences, and encourage participation in limited-time events.